A review of the Urban Village Concept: an operational definition in Malaysia - Samsurijan Mohamad Shaharudin, Awang Azahan, Aiyub Kadarudin, Hussain Mohd Yusoff, (Universiti Pendidikan Sultan Idris, 2017)
A review of the Urban Village Concept: an operational definition in Malaysia by Samsurijan Mohamad Shaharudin, Awang Azahan, Aiyub Kadarudin, Hussain Mohd Yusoff,